Design and Analysis of Fuzzy Controller for UPFC system - Udaya Kumar, L.; C. Ramya, K.; Sivaranjani, S.; Sheeba Rani, S. (International Journal of Engineering and Technology, 2018)
The stability and the transmission ability of a power system can be improved using a Flexible AC Transmission Systems (FACTs) devices. Amongst the various types of FACTs devices, Unified Power Flow Controller (UPFC) provides better controlover the power flow in the transmission line and also increases the stability of the system. At the same time, it also effectively suppress the low frequency oscillations by controlling the voltage and power. Hence in this work, a linearized power system with an UPFC is evaluated. This proposed fuzzy-based UPFC controller affords an effective damping control. The results obtained through simulation shows that the proposed UPFC with fuzzy controller is more effective compared to that of conventional PID controllers. Â Â